Research Note: Reduction of Salmonella load in Brazilian commercial chicken farms using INSPEKTOR®: a bacteriophage-based product - Michael Pino; Karen Mujica; Paola Mora-Uribe; Héctor Garcias-Papayani; Braulio Paillavil; Camilo Avendaño; Diego Flores-Crisosto; Rodrigo Norambuena; Victoria Rojas-Martínez; Matías Aguilera; Nicolás Cifuentes Muñoz; Pablo Cifuentes; et al. (Poultry Science)
Salmonella is a zoonotic pathogen transmitted through food and one of the four leading global causes of diarrheal disease in humans. Brazil is the world's largest exporter of poultry meat, and as such, Brazilian farms routinely detect and prevent Salmonella. The last official monitoring and control in poultry slaughter establishments in Brazil in 2023 detected Salmonella spp. in 14.80 % of samples from chickens, and those Salmonella-positive samples were classified as serovar Minnesota in 65.76 % of samples, serovar Heidelberg in 16.10 % of samples and another 26 or more serovars non-typeable represented a total of 18.13 % of the samples. However, despite these measures, several poultry diseases and outbreaks have been reported in recent decades, requiring permanent disease control. Bacteriophages, which act as specific parasites of bacterial cells, can contribute to food safety. This study evaluated the effectiveness of the INSPEKTOR® phage cocktail for controlling Salmonella on 17 commercial broiler farms on a total of 4 experimental groups (1 control cycle and 3 consecutive treatment cycles) using 3 doses of the cocktail for each cycle. Salmonella load was quantified (DNA copies/mL) by real-time PCR using the invA marker for Salmonella spp., together with serovars Minnesota and Heidelberg, which are relevant to the industry in Brazil. Our results showed that INSPEKTOR® reduced Salmonella load from 0.5 up to 6 logs in the treatment cycles 3 and 4 compared to the control cycle, and reduced the load of Minnesota and Heidelberg in all 3 treatment cycles. This study is relevant as it involves applying a phage cocktail capable of reducing Salmonella load in real poultry production systems with over 3 million broiler chickens.